Adhesive contact between dissimilar cylinders subject to a temperature difference. (July 2016) - Peng, Xiang-Long; Huang, Gan-Yun
Highlights: Adhesive contact between cylinders of different temperature is modeled. Expression of applied force evolving with contact half-width is derived. Thermoelastic effect influences the adhesive contact behaviors significantly. Abstract: In the present work, the adhesive contact between elastic cylinders subject to a temperature difference under a specified applied force is studied. By adopting the concept that the contact size is governed by the balance between the energy release rate and the equivalent work of adhesion, the explicit expression for the applied force with respect to the contact half-width is derived analytically. The pull-off force and the contact half-width at zero applied force as functions of the temperature difference are obtained. The effect of the thermoelastic properties is accounted. Numerical results indicate that both the normal and the tangential thermoelastic effects influence the contact behaviors significantly. The present results may cast light on the evaluation and improvement of some thermal bonding technologies.